The evaluation model of a commercial bank loan portfolio - Mačerinskienė, Irena; Ivaškevičiūtė, Laura (Journal of Business Economics and Management, 2008)
As in other countries where the traditional banking is dominating, the major part of banks’ assets and loan interest income makes a significant share of banks’ income. Inappropriate loan portfolio evaluation might have negative impact on a commercial bank’s performance, the overall banking system, and the economic growth of the country. It is not enough for a bank to have a precise strategy, high lending culture, and observance of general principles to ensure the further growth of profitable loans. It is necessary to apply various evaluation methods of historical and present data, of ratios and factors enabling to implement coherent and comprehensive loan portfolio evaluation, and to encompass different factors as far as possible. Due to a complex business environment and intense competition between banks, it is not enough to evaluate a commercial bank loan portfolio only through the aspect of credit risk, i.e. loss probability level aspect, as is suggested by the scientists. As to every business subject striving for a successful performance and further development, it is essential for a bank to earn profit by financing the other subjects, and to establish the level of assets liquidity. First published online: 14 Oct 2010